Analysis of the company's financial performance using the du pont system and economic value added (EVA) - Prillevawanti, Relita; Reniati; Nugroho, Ari (Institute of Computer Science (IOCS), 2024)
This research aims to determine the company's financial performance using the Du Pont System and Economic Value Added (EVA) methods and to find out whether there are differences in measuring company financial performance between the Du Pont System method and the Economic Value Added (EVA) method. The sampling technique used purposive sampling at state-owned companies in the Construction Industry Sector listed on the IDX in 2017-2021. Based on the results of the analysis, there are differences in measuring financial performance between the Du Pont System method and the Economic Value Added (EVA) method. The results of the research show that the financial performance of BUMN companies in the Construction Industry Sector, when measured using the Du Pont System method, there are 2 companies whose ROI values are above the industry average, namely PT. PP (Persero) Tbk and PT. Wijaya Karya (Persero) Tbk. Meanwhile, the results of the analysis using the Economic Value Added (EVA) method show that PT PP (Persero) Tbk is able to produce the highest average economic value, namely 306,185.